KONFLIK TEOLOGIS DALAM AL-QU'RAN - Wahab, Abdul Jamil; Hariyadi, Muhammad; Tahir, Muhammad Suaib (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
In the Qur’an, there are verses containing the mission of peace (āyāt as-silm) and verses of war (āyāt al-qitāl) or verse of the sword (as-saif verse). Some commentators, some have the view that, the verses of peace have been annulled (nasakh) by the verses of war. If indeed the peace verse is annulled by the war verse, it is considered contrary to the main mission of Islam as the religion of rahmatan li al-‘alamīn or Islam as a religion of peace. The annulment seems to justify the issue of violence in the name of the verses of the Qur’an, so that the Qur’an is accused of being the root for the emergence of violence in people’s lives. Through the mauḍū‘ī approach, it is concluded that the verses of war do not annul the verses of peace and also not vice versa. Each has its own context. Verses of war were revealed in response to the escalating conflict between muslims and the musyrik, ahli kitab, kafir, and hypocrites. War in Islam is permissible when the muslims are oppressed and because they were fought fīrst by musyrik or kafir. If not in war, social relations between muslims and non-muslims are based on the verses of peace, namely, being tolerant, patient, forgiving, yielding, not holding grudges, avoiding disputes, dialogue, guaranteeing freedom and protection, granting amnesty and reconciliation, and live peacefully side by side.